Unlocking Jobs and Growth Through Productivity : A Firm-Level Diagnostic of Albania - World Bank (World Bank, Washington, DC, 2020)
This note takes stock of productivity trends of the Albanian non-agricultural private sector using granular firm-level data. To understand better the sources of jobs and productivity growth, this note analyzes firm-level data from the Albanian annual Structural Business Survey (SBS) collected by INSTAT, the national statistical agency, as well as customs data. This dataset covers all firms with more than ten employees and a representative sample of smaller firms, from all sectors, except for agriculture, financial services and public administration. Despite impressive growth and job creation, both employment and productivity gaps remain. Between 2006 and 2016 the country has seen a doubling of its formal private sector, creating 270,000 jobs. Part of these jobs were genuinely new – total employment in Albania increased by 100,000 jobs in the same time period – while other jobs were the result from people switching from agriculture to manufacturing and services jobs and formalization of informal activities. Employment gaps with the EU remain, even though they have been narrowing in Albania, 40 percent of the labor force works in the formal non-agricultural private sector, against 51 percent in the European Union. To meet the country’s aspirations, the need to create more and especially better jobs prevails. Wages remain the lowest in the region and many young Albanians move abroad to find better job opportunities.